INTELLECTUAL DISTRACTION FOR DYSMENORRHEA - veryudha eka prameswari; ASIROTUL MA’RIFAH; NANING PUJI SURYANTINI; INDAH KUSMINDART (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Dysmenorrhea is a menstrual problem that usually occurs in young women. When dysmenorrhea, interferes with activity, non-pharmacological treatment will be an alternative to reduce dysmenorrhea. One way to deal with pain in a non-pharmacological way is by intellectual distraction, with the theory of reticular activation, which can inhibit pain stimulation when a person receives adequate or excessive sensory input, which results in the inhibition of pain impulses to the brain. Intellectual distraction techniques include filling in crosswords, playing cards, doing hobbies (in bed) such as collecting stamps, writing stories. This study aims to identify the effectiveness of intellectual disorders in reducing dysmenorrhea in young women. This study uses a design that is Quasi-Experiment with a pretest and posttest design without a control group. Population In this study were 122 female students from Mojoanyar Middle School. The sample in this study were all students of Mojoanyar Middle School who experienced dysmenorrhoea who had fulfilled the inclusion criteria of 23 respondents. The tool used to determine changes in the level of pain of respondents is the Face pain rating. The intervention provided was that respondents were asked to fill in the TTS. The collected data was analyzed using SPSS data normality test using the Wilcoxon test with SPSS 23 for Windows. And it was found that before less than half (43.5%) of Intellectual Distraction or 10 respondents experienced mild pain, whereas after being given Intellectual Distraction less than half (34.8%) or 8 respondents experienced mild and moderate pain and no more respondents experienced very severe pain. Therefore young women need to reduce the intensity of menstrual pain by providing Intellectual Distractions techniques with crosswords and accessing them can be through cellphones